The Arens algebras of vector-valued functions - Ganiev, Inomjon; Egamberdiev, Odiljon (Hindawi Publishing Corporation, 2013)
A class of Arens algebras of vector Banach algebra valued functions is considered. It is shown that Arens algebra of vector-valued functions is complete locally convex metrizable algebra.